Blue space exploring the reasons in participating in open water swimming between male and female swimmers - Aleta, Alejandro Bonifacio A. 2001-
Open water swimming, or “Blue Space” is a known sport all around the world (Gerrard, 1999). The population of Filipinos participating in open water events is gradually increasing because of organized events promoting this sport (Jung, 2022). There is, however, no local data characterizing the swimmers who engage in open-water swimming. This research aims to analyze the reasons for the growing number of participation in open water events among Filipinos. This research used a descriptive research design, with a survey questionnaire as the research instrument. The survey included 6 binary question statements for their reason in participating in open water swimming, and were asked to elaborate statements answering “Why?” for their “Yes” responses. The study gathered the responses of the 30 local open water swimmers (15 male and 15 female) with the scope of ages 18 to 66 years old.